ERα-dependent stimulation of LCN2 in uterine epithelium during mouse early pregnancy. Issue 4 (April 2020) - Liu, Y-F; Li, M-Y; Yan, Y-P; Wei, W; Li, B; Pan, H-Y; Yang, Z-M; Liang, X-H
Abstract : Maintenance of a suitable uterine milieu is important for embryo development and subsequent implantation during early pregnancy. High estrogen level in proestrous and estrous stages is essential for uterine anti-bacterial activity during preimplantation period. Lipocalin-2 is an essential molecule which prevents bacterial infection by sequestering iron. In this study, the highest expression of lipocalin-2 is observed in the endometrial epithelium on day 1 of normal pregnancy and pseudopregnancy, which exhibit a similar hormone scenario. By injecting the agonists for estrogen receptor α and estrogen receptor β in ovariectomized mice, we found estrogen receptor α is the dominant member for estrogen regulation on lipocalin-2 expression. Estrogen treatment in estrogen receptor α-knockout mice further confirmed the role of estrogen receptor α. Using published data from whole-genome estrogen receptor α binding site assay, significant estrogen receptor α recruitment peaks are found at the downstream of lipocalin-2 gene after estrogen treatment. Furthermore, to study the anti-bacterial activity of lipocalin-2 in uterus, Escherichia coli is injected to mimic bacterial infection. Our results showed an obvious induction of lipocalin-2 in Escherichia coli -treated group. Taken together, this study indicates estrogen regulation of lipocalin-2 in uterine epithelium is mediated by estrogen receptor α, and lipocalin-2 may have anti-bacterial activity during early pregnancy.